Effect of Human Endothelial Progenitor Cell (EPC)- or Mouse Vascular Endothelial Growth Factor-Derived Vessel Formation on the Survival of Vitrified/Warmed Mouse Ovarian Grafts. (July 2014) - Cha, Soo Kyung; Shin, Dong Hyuk; Kim, Bo Yeun; Yoon, Sook-Young; Yoon, Tae Ki; Lee, Woo Sik; Chung, Hyung Min; Lee, Dong Ryul
The aim of this study was to evaluate the effectiveness of improving angiogenesis at graft sites on the survival of follicles in transplanted ovarian tissue. Matrigel containing 5 × 10 5 of cord blood-derived endothelial progenitor cells (EPCs) or 200 ng of mouse vascular endothelial growth factor (VEGF) was injected subcutaneously into BALB/c-Nu mice. After 1 week, vitrified/warmed ovaries from female B6D2F1 mice were subcutaneously transplanted into the injection sites. After 1, 2, and 4 weeks posttransplantation, the ovaries were recovered and subjected to histological analysis. Oocytes were collected from the transplanted ovaries, and their fertilization, embryonic development, and delivery were also observed. Vitrified/warmed ovaries transplanted into EPC- or VEGF-treated sites developed more blood vessels and showed better follicle survival than those transplanted into sham-injected sites. Normal embryonic development and consequent live births were obtained using oocytes recovered from cryopreserved/transplanted ovaries. Treatment with EPCs or VEGF could prevent the ischemic damage during the early revascularization stage of ovarian transplantation.